Privatization, efficiency and integration: The truth about the Paraguay-Paraná Waterway in Argentina in the 1990’s - Rausch, Gisela Ariana (2021)
The Paraguay-Paraná Waterway program (HPP in Spanish), was a large scale infrastructure project which intended to attract global investment to five South American countries and intensify the extraction of “natural resources”, for export to major world production centers. This article examines the discursive strategies deployed in Argentina during the 1990’s, by the sponsors of the project in their efforts to establish a specific “truth” supporting their efforts to appropriate the territory. This research combines the approaches of disciplines such as human geography and political ecology. The historical object of the study is based on documentary sources and shows that the dominant discourse about the HPP was built around three main ideas: privatization, efficiency and regional integration. The first two revolve around the notion of “State failure” and the third reshapes the ideology of regional integration from a neo-liberal perspective. These guiding ideas took particular nuances in Argentina´s specific historical and economic conditions and were able to help impose this extractive project, without having to face any significant opposition.